West Virginia Regulatory Program (The Federal Register / FIND, 2009)
Interim rule with request for comments. CFR Part: "30 CFR Part 948" Citation: "74 FR 36113" Document Number: "WV-115-FOR; OSM-2009-0006" Page Number: "36113" "Rules and Regulations" SUMMARY: We are approving, on an interim basis, an amendment to the West Virginia regulatory program (the West Virginia program) under the Surface Mining Control and Reclamation Act of 1977 (SMCRA or the Act). West Virginia revised its Surface Coal Mining and Reclamation Act to effect changes concerning its alternative bonding system. The tax provisions of the amendment are intended to increase and extend the special reclamation tax, subject to biennial review by the legislature, and remove the additional tax. We are approving the increase and extension of the special reclamation tax, at the rate of fourteen and four-tenths cents per ton of clean coal mined, for deposit in the Special Reclamation Fund and the Special Reclamation Water Trust Fund, on an interim basis, with our approval becoming effective upon publication of this interim rule.